AVALIAÇÃO DA INFESTAÇÃO POR Singhiella simplex (HEMIPTERA: ALEYRODIDAE) EM Ficus benjamina NO MUNICÃPIO DE SÃO PAULO, SP, BRASIL - Velasco, Giuliana Del Nero; Moura, Rogério Goularte; Berti Filho, Evoneo; Couto, Hilton Thadeu Zarate do (REVISTA DE AGRICULTURA, 2016)
AVALIAÇÃO DA INFESTAÇÃO POR Singhiella simplex (HEMIPTERA: ALEYRODIDAE) EM Ficus benjamina NO MUNICÃPIO DE SÃO PAULO, SP, BRASIL